Lorna Mott comes home : a novel - Johnson, Diane, 1934- (Alfred A. Knopf, 2021)
"A comedic novel about an American woman leaving her 20-year marriage to her French husband, returning to her native San Francisco to pick up the life she left behind, and the entwining lives of her children and grandchildren"--